Money Politic, Gratifikasi, Dan Hadiah Perspektif Al-Isfahani Dalam Kitab Al-Mufradât Fî Gharîb Al-Qur’ân - Saefudin, Asep; Muid N, Abd.; Kerwanto, Kerwanto (Jurnal Global Ilmiah, 2025)
The Qur'an condemns money politics and gratuities as reprehensible practices. These are considered to involve the wrongful use of wealth (al-akl bi al-bâthil), al-suht (consuming wealth through manipulation of the truth), al-hadiyyah (gifts that have the potential to create conflicts of interest), al-ghulûl (misuse of authority), yasytarûna bihî tsamanan qalîla (manipulating the truth for worldly gain), and al-khiyânah (abuse of power). Most interpreters associate these key terms with bribery (risywah), which differs from gifts, a practice regarded as commendable in the Qur'an. However, caution is advised as the term "gift" has long been manipulated to mean bribery.Criticism of the above practices, because they contain actions that are contrary to maqâsid shari'ah (Islamic sharia principles) such as the principle of safeguarding property (hifzh al-mâl) and safeguarding religion (hifzh al-dîn). Money politics and gratuities are a means of spreading haram money. The practice turns money, which was initially something that could help people's lives, into something that is haram to use because of prohibited transactions. Money politics and gratuities are a form of neglect of religious teachings, if done means that someone is leaving their religion.